2018
DOI: 10.4102/jef.v11i1.160
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the technical efficiency of the banking system

Abstract: The study investigated the technical efficiency of the commercial banks in Zimbabwe during the period 2009–2015. The study entailed the decomposition of the technical efficiency into pure technical and scale efficiency to understand the sources of the technical inefficiency in the commercial banks in Zimbabwe. To accomplish the task, the study sampled 11 commercial banks of which 6 are domestic and the other 5 are foreign banks. The study used the data envelopment analysis method. The results of the study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…It assesses how far a firm can reduce its inputs (in a fixed proportion) while remaining within the variable return to scale (VRS) frontier (Iqbal & Awan, 2015). Scale efficiency, on the other hand, refers to the relationship between the output level and average cost; thus, it is related to the size of an organization's operation (Abel & Bara, 2017). It is a parameter that indicates a firm's operation at an optimum scale size (Huguenin, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…It assesses how far a firm can reduce its inputs (in a fixed proportion) while remaining within the variable return to scale (VRS) frontier (Iqbal & Awan, 2015). Scale efficiency, on the other hand, refers to the relationship between the output level and average cost; thus, it is related to the size of an organization's operation (Abel & Bara, 2017). It is a parameter that indicates a firm's operation at an optimum scale size (Huguenin, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Firms that can change their output level should use this model orientation (Forbes et al, 2010). Indeed, the orientation of output and input determines the point on the efficient frontier to use as a benchmark (Abel & Bara, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The bank faces the dilemma of undersizing (oversizing) to increase (decrease) returns to scale, resulting in operations below (above) the ideal size. If the output changes appropriately with the growth or reduction in inputs, the organization is scale efficient (Abel and Bara, 2017).…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…Beck et al (2013) found that there is a higher degree of foreign bank penetration in low and middle-income countries as compared to high-income countries both in terms of number and assets of foreign banks. Abel et al (2017) pointed out that the banking and financial systems in low-income countries and middle-income countries are less open internationally compared to higher-income countries. In terms of bank ownership, Dietrich and Wanzenried, (2011) found that the public ownership of banks is higher in lowincome countries than in middle-or high-income countries, as 20% of all banks in low-income countries are either fully or partially owned by the state.…”
Section: Bank Efficiency and Countries Income Classificationsmentioning
confidence: 99%